1988
DOI: 10.1007/bf01655678
|View full text |Cite
|
Sign up to set email alerts
|

Results of gastric resection for carcinoma of the stomach: The European experience

Abstract: A European state of the art in the treatment of gastric cancer is presented from the results of a questionnaire. Data were obtained from 62 centers, 60% of which were from abroad and 40% of which were from Germany, reporting a total of 16,594 patients. A feature was a low portion (8.8%) of early cancer. The operation preferred was total gastrectomy. Only in the case of antral carcinoma of the intestinal type, according to Laurén, would the majority perform subtotal gastrectomy. Staging of lymph nodes was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
1
8

Year Published

1990
1990
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(49 citation statements)
references
References 12 publications
2
38
1
8
Order By: Relevance
“…Similar results were reported by other authors (25,36,37). Although Japanese surgeons routinely perform extended lymphadenectomy for gastric cancer patients without distant metastasis, many western investigators have reported that D2 or more extended lymphadenectomy could not improve the prognosis of gastric cancer significantly compared with D1 lymphadenectomy, which is generally accepted by surgeons in western countries (38)(39)(40)(41)(42)(43). Nevertheless, other investigators have stated that D2 lymph node dissection might improve the survival of patients with lymph node-negative gastric carcinoma (25,44,45).…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were reported by other authors (25,36,37). Although Japanese surgeons routinely perform extended lymphadenectomy for gastric cancer patients without distant metastasis, many western investigators have reported that D2 or more extended lymphadenectomy could not improve the prognosis of gastric cancer significantly compared with D1 lymphadenectomy, which is generally accepted by surgeons in western countries (38)(39)(40)(41)(42)(43). Nevertheless, other investigators have stated that D2 lymph node dissection might improve the survival of patients with lymph node-negative gastric carcinoma (25,44,45).…”
Section: Discussionmentioning
confidence: 99%
“…This relatively small survival benefit must be considered against the increased operative risks of extended lymphadenectomy. Although the operative mortality rate of 2% associated with the ELND procedure seems to be acceptable, some researchers have reported that more aggressive surgery may be related to higher operative morbidity and mortality (Diggory and Cuschieri, 1985;Heberer et al, 1988;Dent et al, 1988). In addition, the ELND procedure presents the disadvantage of longer operation time and greater blood loss, although these factors were not associated with any increase in the mortality rate (de Aretxabala et al, 1987;Smith et al, 1991;Pacelli et al, 1993).…”
Section: Survivalmentioning
confidence: 99%
“…Japanese surgeons normally perform extensive lymphadenectomy for EGC because a certain proportion of these patients have lymph nodal involvement and carcinoma recurrence is not rare. In contrast, most surgeons in Western countries do not use aggressive surgery (Cuschieri, 1986;Heberer et al, 1988;Irvin and Bridger, 1988;Heesakkers et al, 1994), perhaps because of uncertainty regarding improvement in the survival rate and the high operative risk associated with extensive lymph node dissection (Dent et al, 1988;Heberer et al, 1988;Irvin and Bridger, 1988).To evaluate the therapeutic value of extensive lymphadenectomy in EGC, we analysed retrospectively the causes of death after surgery and compared the 10 year disease-specific survival rate in patients who had received extensive lymphadenectomy with patients who had received simple gastric resection. (LLND).…”
mentioning
confidence: 99%
“…In Europe and the United States, considerably lower rates 8.8% and 4% of all resected cases, respectively, have been reported [12,13] which suggests that some EGC are being missed in Western countries. However, recent studies [7,14] describe an increasing frequency of diagnosed EGC in Western countries.…”
Section: Introductionmentioning
confidence: 96%